Women's entrepreneurial competence within a patriarchal social system - Hilmiana Hilmiana; Devi Alviani (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
Women in patriarchal social systems face various challenges that affect their economic access and hinder their empowerment. This research aims to identify the competencies required by women to thrive within a patriarchal social system, reduce gender disparities, and promote empowerment in various aspects of life. This research utilized secondary data from the Scopus database and applied a document study method. Keywords used for the search included "women competence," "women skills," "women entrepreneur skills," "entrepreneurial competencies," and "entrepreneur competence." After filtering, 31 articles were selected for analysis. The analysis used the Miles and Huberman model, including reduction, data analysis, and conclusion. The findings indicate that to address the challenges of patriarchy and achieve empowerment, women need to develop multidimensional competencies involving entrepreneurial skills, commitment, high-level conceptual abilities, recognition of opportunities, organization, relationships, strategic thinking, and marketing. The challenges of norms and gender expectations in patriarchal societies become obstacles that need to be overcome by educating the community about the vital role of women and the competencies required in SMEs (Small and Medium Enterprises). Innovation, creativity, and innovative marketing strategies are key to success, while support and networks from stakeholders can provide valuable boosts.